Kepemimpinan Efektif KH. Agus Mubaraak di Pondok Pesantren Sabiilunnaja - Amalia, Ulfah; Solahudin, Dindin; Yulianai, Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2021)
Agus Yudhi Mubaarak in the management of Islamic boarding schools, K. H. Agus Yudhi Mubaarak’s program in the management of Islamic boarding schools, and the implementation of the K. H. Agus Yudhi Mubaarak program in the management of Islamic boarding schools. This study uses a descriptive method with a qualitative approach. The results of the study found that the progress of the Sabiilunnaja Islamic boarding school was inseparable from the strategy formulated by K. H. Agus Yudhi Mubaarak, namely by introducing the nature of Rububiyah, also introducing the habit of synergizing between horizontal and vertical relations and increasing intellectualism and spiritualism. Then the strategy is modeled on the activities of the santri programs. Among them are short, medium and long term programs. The implementation of the program went smoothly, which of course involved all students and the board of teachers. Thus, all santri activities are the basis for the development of the Sabiilunnaja Islamic Boarding School which is managed by K. H. Agus Yudhi Mubaarak in the management of Islamic boarding schools.